Brief behavioral self-regulation counseling for HIV treatment adherence delivered by cell phone: an initial test of concept trial. - Kalichman, Seth C; Kalichman, Moira O; Cherry, Chauncey; Swetzes, Connie; Amaral, Christina M; White, Denise; Jones, Mich'l; Grebler, Tamar; Eaton, Lisa (AIDS patient care and STDs, 2011)
Affordable and effective antiretroviral therapy (ART) adherence interventions are needed for many patients to promote positive treatment outcomes and prevent viral resistance. We conducted a two-arm randomized trial (n = 40 men and women receiving and less than 95% adherent to ART) to test a single office session followed by four biweekly cell phone counseling sessions that were grounded in behavioral self-management model of medication adherence using data from phone-based unannounced pill counts to provide feedback-guided adherence strategies. The control condition received usual care and matched office and cell phone/pill count contacts. Participants were baseline assessed and followed with biweekly unannounced pill counts and 4-month from baseline computerized interviews (39/40 retained). Results showed that the self-regulation counseling delivered by cell phone demonstrated significant improvements in adherence compared to the control condition; adherence improved from 87% of pills taken at baseline to 94% adherence 4 months after baseline, p < 0.01. The observed effect sizes ranged from moderate (d = 0.45) to large (d = 0.80). Gains in adherence were paralleled with increased self-efficacy (p < 0.05) and use of behavioral strategies for ART adherence (p < 0.05). We conclude that the outcomes from this test of concept trial warrant further research on cell phone-delivered self-regulation counseling in a larger and more rigorous trial.
Keywords: Adult; Aged; Cellular Phone; Counseling; Drug Administration Schedule; Female; Follow-Up Studies; HIV Infections; Humans; Intervention Studies; Male; Medication Adherence; Middle Aged; Self Care; Self Efficacy; Social Control, Informal; Socioeconomic Factors; Treatment Outcome